Análisis de la gestión de riesgos en proyectos de Ingeniería Civil aplicando la Inteligencia Artificial (2024)
The development of this methodological research will be descriptive with a methodical approach, with the purpose of providing a broad and objective understanding of risk management in Civil Engineering projects through the use of Artificial Intelligence (AI). This compilation monograph promotes independent discussion and reflection, as suggested by Mario Bunge (1959). The objectives are oriented towards a detailed theoretical review on the application of AI in the management of Civil Engineering projects, revealing the attention of research on the integration of risks with AI in this field, with greater emphasis on other domains and fields of action.